SPAREPART MOTOR SALES APPLICATION SHOP PANDROLTECH ON USING PHP & MY SQL - Melya Novita; Hariyanto Hariyanto, SKom, MMSI (Jurnal Sistem Informasi, 2008)
This explains the scientific writing about the creation of dynamic web-based applications online sales as a means or media commerce over the Internet using PHP and MySQL. Making web-based application is intended to help enable customers to shop in motor spare parts ordering transaction at this Pandroltech store. To complete the creation of this web-based applications using literature studies, both authors of books or the Internet as a reference and comparison. Ease of transactions via the Internet is possible because of the dynamic web-based programming that strongly support the sales transaction.